1958
DOI: 10.1126/science.128.3329.898
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Perceived Color of Very Bright Stimuli

Abstract: nide-sensitive terminal respiratory pathway. The other, in which menadione or other electron acceptors can function, does not involve the cyanide-sensitive pathway, but rather a diaphorase type flavoprotein-catalyzed cyanide-insensitive reaction. l\10RTON 1\1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1962
1962
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…This quenching persists for some 20 min, and occurs also in human rod visual purple (Weale, 1962). The existence of this quenching effect shows that the photo-55P PROCEEDINGS OF THE sensitivities of the foveal pigments and of visual purple are equal to within a few per cent (Weale, 1965) and all but harmonizes our data on the Brucke-Bezold phenomenon (Weale, 1964) and those obtained in great detail by Cornsweet, Fowler, Rabedean, Whalen & Williams (1958 Chemical measurements have shown that the stomach of the foetal rabbit is absorbing Na against its gradient of electrochemical potential from the 20th day of gestation (and possibly before). From the 23rd day, H and Cl ions were also found to be secreted into the stomach against their gradients of electrochemical potential (Wright, 1961(Wright, , 1963.…”
Section: Psupporting
confidence: 84%
“…This quenching persists for some 20 min, and occurs also in human rod visual purple (Weale, 1962). The existence of this quenching effect shows that the photo-55P PROCEEDINGS OF THE sensitivities of the foveal pigments and of visual purple are equal to within a few per cent (Weale, 1965) and all but harmonizes our data on the Brucke-Bezold phenomenon (Weale, 1964) and those obtained in great detail by Cornsweet, Fowler, Rabedean, Whalen & Williams (1958 Chemical measurements have shown that the stomach of the foetal rabbit is absorbing Na against its gradient of electrochemical potential from the 20th day of gestation (and possibly before). From the 23rd day, H and Cl ions were also found to be secreted into the stomach against their gradients of electrochemical potential (Wright, 1961(Wright, , 1963.…”
Section: Psupporting
confidence: 84%
“…Purdy's observations, however, were made on only moderate to high intensity long-wavelength fields. At very high intensities, the apparent color of a long-wavelength field gradually changes from red to yellow and finally to green, which remains the Bsteady-state[ appearance (Auerbach & Wald, 1955;Cornsweet, Fowler, Rabedeau, Whalen, & Williams, 1958). Indeed, we also observe that very intense long-wavelength backgrounds (above the transition from +sLÀsM to ÀsL+sM) obtain a green tinge under steady-state conditions.…”
Section: Physiological Considerationsmentioning
confidence: 59%
“…(This transition and a model related to the one shown in Figure 11 were proposed in 2006 and discussed in detail in Stockman & Plummer, 2005a. ) Indeed, at very high intensities, the hue of a long-wavelength field gradually changes from red to yellow and finally to green, which remains the steady-state appearance (Auerbach & Wald, 1955;Cornsweet et al, 1958).…”
Section: A Working Modelmentioning
confidence: 99%
“…On long-wavelength backgrounds of low to moderate intensity, we suppose that the L-cones are suppressed relative to M-cones by the background fields, so that network signals through M-cones will predominate, thus favoring the ÀsM and þsL that travel though M-cones (see below). On intense long-wavelength backgrounds on which the L-cones are significantly bleached but the M-cones are not, and the background hue shifts towards yellow or green (Auerbach & Wald, 1955;Cornsweet, Fowler, Rabedeau, Whalen, & Williams, 1958), we suppose that the relative M-cone sensitivity losses start to exceed those of the L-cones, thus switching the balance to favor ÀsL and þsM signals through L-cones (Stockman & Plummer, 2005a). Similarly, on short-wavelength backgrounds, we suppose that the M-cones are relatively suppressed by the background fields, so that network signals through L-cones predominate, thus also favoring ÀsL and þsM signals.…”
Section: Introductionmentioning
confidence: 99%